Gambaran Status Gizi Dan Kebiasaan Sarapan Siswa di SMP Negeri 1 Bangli - Swandewi, Kadek Dian; Nursanyoto, M.Kes, Ir. Hertog; Widarti, DCN, M.Kes, I Gusti Agung Ari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Teenagers' balanced nutrition will greatly determine their maturity in the future. Teenagers' balanced nutrition needs special attention. Teenage nutrition problems are caused by several factors, including breakfast patterns. This research aims to determine the nutritional status and breakfast habits of students. This research is an observational type. With a cross sectional design. The population is all students at SMP N 1 Bangli. A sample of 76 subjects was selected randomly. Data was collected using questionnaires and the SQFFQ form. Based on the research results, it shows that more than half of the students at SMP Negeri 1 Bangli have good nutritional status, 54 people (55.26%). Than half of the students at SMP Negeri 1 Bangli had breakfast habits that were not according to recommendations, namely 41 people (53.95%). Breakfast habits are not as recommended, more people are obese. The type consumed in more or less obese category. The amount consumed in the more or less obese category. The frequency consumed in the rare category is greater that of those with poor nutrition. Considering the importance of breakfast on nutritional status, it is recommended to socialize the benefits of breakfast regularly and continuously.